2009
DOI: 10.1177/1076029608330472
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Impact of VKORC1 and CYP2C9 Allelic Variants on Warfarin Dose Requirements in a Hispanic Population Isolate

Abstract: Warfarin is the most prescribed oral anticoagulant worldwide. Because of the complexity of warfarin therapy, we attempted to dissect genetic from bioenvironmental factors influencing warfarin dose responses in individuals of a genetic isolate of Hispanic ancestry. A total of 191 patients with standard values of international normalized ratio were recruited. Three groups with a significantly different warfarin dose response were identified, that is, sensitive (2.28 +/- 0.50 mg/d), intermediate (4.2 +/- 0.76 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
4
10
0
3
Order By: Relevance
“…La región Andina se caracteriza por el predominio de individuos caucásicos mestizos (30), que según las estimaciones corresponden a 85,9 % de los habitantes de Colombia (31). Por otra parte, a pesar de pequeñas diferencias, el porcentaje de genotipos con el polimorfismo en forma heterocigótica u homocigótica en la posición -1639 del VKORC1, fue similar al publicado en estudios llevados a cabo en población colombiana de Bogotá, Risaralda (21), y Antioquia (20). Lo mismo se observó con los polimorfismos en el gen CYP2C9.…”
Section: Discussionunclassified
“…La región Andina se caracteriza por el predominio de individuos caucásicos mestizos (30), que según las estimaciones corresponden a 85,9 % de los habitantes de Colombia (31). Por otra parte, a pesar de pequeñas diferencias, el porcentaje de genotipos con el polimorfismo en forma heterocigótica u homocigótica en la posición -1639 del VKORC1, fue similar al publicado en estudios llevados a cabo en población colombiana de Bogotá, Risaralda (21), y Antioquia (20). Lo mismo se observó con los polimorfismos en el gen CYP2C9.…”
Section: Discussionunclassified
“…A multitude of retrospective [14][15][16][17][18][19][20][21][22][23] and prospective [11,[24][25][26][27][28][29][30][31][32][33][34] studies conducted since, have now clearly established the significant influence of polymorphism in CYP2C9 [9-11, 14, 15, 23, 24, 26, 28, 29, 32] and VKORC1 [9,10,23,26,28,32] genes on metabolism, and hence, the anticoagulant activity of warfarin. Thus, individuals homozygous for the CYP2C9*1 allele require a higher maintenance dose compared to the CYP2C9*2 (R 144 C) and CYP2C9*3 (I 359 L) homozygotes, respectively.…”
Section: Warfarin Metabolism and Pharmacogenomicsmentioning
confidence: 99%
“…However, additional studies with larger cohorts [20,33,34] have allowed researchers to define two haplotyes composed of at least six variations across the entire coding as well as non-coding regions of the VKORC1 gene. Individuals homozygous for haplotype A are characterized by a resistant phenotype, whereas individuals homozygous for haplotype B exhibit a sensitive phenotype, the heterozygous subjects showing an intermediate response.…”
Section: Warfarin Metabolism and Pharmacogenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the influence of the variant genotype of the VKORC1 -1693 G>A polymorphism was demonstrated on the therapeutic dose of acenocoumarol or warfarin. [14][15][16] Moreover, the involvement in the development of arterial and venous embolic events has also been studied. Studies have shown that patients with VKORC polymorphism mutant genotypes are at high risk of stroke and coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%